Diagnóstico social: um instrumento de pesquisa sobre populações e territórios - Siqueira, Renata Oliveira de (2016)
This paper presents an analysis of the way the third sector and non-governmental organizations - NGOs have been dialoguing with the public and the territory they serve, especially under the focus tool social diagnosis, instrument technically addresses social issues and causalities to the phenomena observed in the localities. Therefore, it is carried out a literature review on the tool and the Third institutionalized context Sector and NGOs and a picture of the realization of the Social Diagnosis by Instituto Bola Pra Frente 2016.